S41 Incidence of SARS-CoV-2 and non-SARS-CoV-2-associated community acquired lower respiratory tract infections in Bristol, UK: a prospective cohort study. (11th November 2022) - Hyams, C; Challen, R; Begier, E; Southern, J; King, J; Morley, A; Szasz-Benczur, Z; Garcia Gonzalez, M; Kinney, J; Campling, J; Gray, S; Oliver, J; et al.
Abstract : Background: The novel pathogen SARS-CoV-2 and associated public health control measures have affected acute lower respiratory tract disease (aLRTD) epidemiology. We sought to compare the incidences of respiratory infection hospitalizations with and without SARS-CoV-2 infection during the pandemic. Methods: We undertook a prospective cohort study of adults (≥18 y) hospitalised at both Bristol secondary care NHS Trusts from August 2020–November 2021, encompassing the end of the first UK wave (ancestral SARS-CoV-2 strain) and subsequent Alpha and Delta waves. Patients with ≥2 of 8 aLRTD signs/symptoms (e.g., cough, pleurisy, dyspnoea) or a clinical or radiological diagnosis consistent with aLRTD (e.g., pneumonia) were included. Results: Among 12557 adult aLRTD hospitalisations, 10087 (80%) had infective aLRTD (i.e., pneumonia or non-pneumonic lower respiratory tract infection [NP-LRTI]), 2161 (17%) had non-infective cause (e.g., COPD/HF exacerbations only), and 306 (2.4%) an undetermined diagnosis. Thirty-two percent (3178/10087) of hospitalized infective aLRTD involved confirmed SARS-CoV-2 infection. Annual pneumonia incidence (per 100, 000 adults) was 714·1 (264·2 SARS-CoV-2-associated, 449·9 non-SARS-CoV-2) and NP-LRTI incidence was 346·2 (43·8 SARS-CoV-2-associated, 302·4 non-SARS-CoV-2). Although SARS-CoV-2-associated aLRTD was more frequent than non-SARS-CoV-2 infective aLRTD during COVID-19 surges, non-SARS-CoV-2 NP-LRTI was more common in all age groups overall, and non-SARS-CoV-2 pneumonia incidence among those aged 65–74, 75–84, and 85+ years was 1.9, 2.8 and 3.8-fold higher than COVID-19-associated pneumonia. SARS-CoV-2 infection incidence displayed high variability (range: 0–221 cases/week), while other infective aLRTD events' frequency was more stable (range: 71–152 cases/week). Whilst SARS-CoV-2-related hospitalisation trends followed community COVID-19 frequency, non-SARS-CoV-2 respiratory infection admissions showed no association. Conclusions: While SARS-CoV-2 infection was a large component of hospitalised aLRTD, non-SARS-CoV-2 infection caused 56% of respiratory infection hospitalisations overall. Measured incidences of non-SARS-CoV-2 pneumonia and NP-LRTI were higher than pre-pandemic UK estimates. Given public health interventions to reduce all infective aLRTD implemented during this year, these higher estimates likely reflect highly comprehensive surveillance although there may have been a true higher non-SARS-CoV-2 disease incidence. These results demonstrate the significant burden of acute respiratory infection on healthcare systems. Broader efforts to prevent and manage all forms of adult aLRTD should be prioritized in addition to current COVID-19 prevention efforts. Please refer to page A209 for declarations of interest related to this abstract.